Analisis Forensik Konten dan Timestamp pada Aplikasi Tiktok - Fauzan Natsir (Universitas Indraprasta PGRI Jakarta, 2021)
The Tiktok application is one of the social media platform applications that often finds many loopholes to get the identity of the application's users. TikTok has experienced tremendous growth by reaching 1.5 billion users in 2019. This research uses an Open-Source Intelligence (OSINT) method as a standard in the research phase to reveal the timestamps obtained from the TikTok application. The method used in this research is the National Institute of Standard Technology (NIST). The research uses forensic tools, namely Browser History Capture/Viewer, Video Cache Viewer, Unfurl and Urlebird. The result of this research shows a complete description of all digital artifacts and timestamps obtained from TikTok content. Furthermore, by using the results of the analysis in the research, it is expected that the research can help to reconstruct the content and to search for keywords from the timestamp in the TikTok application.